A Qualitative Study on Voices of South African Learner Nurses on Occupational Health and Safety during Clinical Learning: Pre-COVID-19 Pandemic - Livhuwani Muthelo; Tshepo Albert Ntho; Masenyani Oupa Mbombi; Thabo Arthur Phukubye; Mamare Adelaide Bopape; Tebogo Maria Mothiba (MDPI AG, 2023)
The demanding and complex training of learner nurses in clinical practices requires various occupational health and safety measures to curb occupational health hazards among learner nurses. This paper aimed to explore learner nurses' experiences concerning occupational health and safety during clinical learning. A qualitative descriptive, contextual and exploratory design study was conducted. A total of 31 learner nurses were selected using purposive sampling. Data were collected by semi-structured interviews and analysed using Tesch's open coding method. Two themes emerged from this study: "The experiences of learner nurses concerning their health and safety during clinical learning" and "The measures to be taken to promote occupational health and safety during clinical learning." Highlighting challenges and measures to mitigate occupational health hazards among learner nurses in the South African context, Limpopo province, would be beneficial. The findings can assist stakeholders in developing specific precautionary guidelines for learner nurses. Effective and innovative occupational health and safety training programmes for learner nurses can be developed despite constrained environmental resources.